Critical Perspectives on the Scholarship of Assessment and Learning in Law Volume 1: England - Bone, Alison; Maharg, Paul (ANU Press, 2019)
"The Assessment in Legal Education book series offers perspectives on assessment in legal education across a range of Common Law jurisdictions. Each volume in the series provides: Information on assessment practices and cultures within a jurisdiction. A sample of innovative assessment practices and designs in a jurisdiction. Insights into how assessment can be used effectively across different areas of law, different stages of legal education and the implications for regulation of legal education assessment. Appreciation of the multidisciplinary and interdisciplinary research bases that are emerging in the field of legal education assessment generally. Analyses and suggestions of how assessment innovations may be transferred from one jurisdiction to another. The series will be useful for those seeking a summary of the assessment issues facing academics, students, regulators, lawyers and others in the jurisdictions under analysis. The exemplars of assessment contained in each volume may also be valuable in assisting cross-jurisdictional fertilisation of ideas and practices. This first volume focuses on assessment in law schools in England. It begins with an introduction to some recent trends in the culture and practice of legal education assessment. The first chapter focuses on the general regulatory context of assessment and learning in that jurisdiction, while the remainder of the book offers useful exemplars and expert critical discussion of assessment theories and practices. The series is based in the PEARL Centre (Profession, Education and Regulation in Law), in The Australian National University's College of Law. "